PERSPECTIVE DIRECTIONS OF OSTEOARTHRITIS THERAPY - L. I. Alekseeva; E. M. Zaitseva (Научно-практическая ревматология)
The paper discusses the new mechanisms of osteoarthritis (OA) pathogenesis. Particular emphasis is placed on the role of subchondral bone remodeling, inflammatory mediators, bone morphogenetic proteins, etc. These data may be of great importance for elaborating new approaches to OA treatment.